Gender dan Mekanisasi: Pengalaman Pekerja Perempuan Berpartisipasi dalam Kelompok Petik Mesin di Perkebunan Teh Gambung, Jawa Barat - Kralawi Sita (Universitas Padjadjaran, 2019)
Mechanization in the tea harvesting process commonly leads to gender imbalance, as male workers receive more benefit than female. However, this phenomenon does not the case in Gambung Tea Plantation. Female participation in the machine harvesting is high as they become the operator of tea plucking machines. This phenomenon is worth to study in particular to explore female workers’ personal experience in mechanical tea plucking. This research applies descriptive qualitative method with phenomenology approach. Female and male machine picker becomes the main subject in this study. Primary data were collected through observation, documentation, interviews and Focused Group Discussion with female and male tea plucker. Triangulation techniques were applied to ensure data validity. This study suggests that the mechanization process in Gambung Tea Plantation has created a new gender division of labour where male and female work together in a team to operate the machine. Female workers show quality of work better than male worker. Amidst the efforts of female workers to participate in the mechanization there are risks and constraints for them, such as less-gender friendly equipment, lack of access and control to resources, cultural norms, values in the society.